PROFIL PASIEN ULKUS DIABETIKUM YANG DIRAWAT DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE 1 JANUARI-31 DESEMBER 2011 - Syadzwina Syaufika; Jazil Karimi; Suyanto ' (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Diabetes mellitus (DM) is a group of metabolic disease which characterized byhyperglycemia, caused by insulin secretion or insulin activity disorder or both.Uncontrolled DM could cause many complications, one of them is diabetic ulcer. Thesample was 39 patients using total sampling. In conclusion,characteristics of respondentsby sex diabetic ulcer patients obtained 56.42% were females, age group <60 yearsobtained 82%, and duration of suffering DM obtained 48.72% 0-5 years. Distribution ofdiabetic ulcers based on fasting blood sugar obtained 93.93% is bad.. Diabetic ulcersdistribution based on the location of 47.91% was obtained at toes, feet and back legsrespectively 16.67%, 10.41% ,other areas and heel respectively 8.33%. Distribution ofdiabetic ulcer based on Wagner criteria was obtained 33.3% Grade 4, Grade 3 obtained25.6%, 23.1% obtained Grade 5, Grade 2 obtained 10.3%, 7.7% obtained Grade 1 andGrade 6 obtained 0%. Distribution of diabetic ulcer based on length of stay obtained63.15% were> 7 days, 3-7 days obtained 28.94%, and <3 days gained 7.89%. Distributionof diabetic ulcer based on therapy obtained 89.7% were non-surgical, and surgical therapyobtained 10.3%.Keywords: DM, diabetic ulcer, profile.